Penerapan Tax Review Atas Pajak Penghasilan PT. First Health Enterprises Pada Tahun 2019 - Kadek Widyawati; I Wayan Sudiana (UNHI Press, 2022)
Tax review is an act of reviewing all company transactions to find out that taxobligations are in accordance with applicable regulations. This research was conducted by corporate taxpayers, namely PT. First Health Enterprises, which is engaged in healthservices provided by paramedics, which was established in 2016 with a turnover orgross income of under 4.8 billion per year. The purposeof this study is to carry out a strategy in tax planning in order to minimize the tax burden and minimize audits byassessing the activities of taxpayers' overall obligations in accordance with applicabletax rules. This study uses a comparative descriptive analysis technique. Calculationof Tax review at PT. First Health Enterprises uses comparisons between financialstatements, tax returns that have been reported, proof of tax payment and proof of tax reporting which are then reviewed according to tax regulations on tax objects, tax rates,timeliness of deposit and reporting, and tax reconciliation. Based on the results of the tax review of PT. First Health Enterprises stated that there is an estimated contingent liability of PT. First Health Enterprises amounting to Rp. 11,807,632 with potentialsanctions and administrative fines for late reporting and late payments of Rp. 6,205,390 but this amount is still an estimate, this shows that PT. First Health Enterprises has not been 100% compliant in carrying out income tax tax obligations article 21, 23, 4 paragraph (2) on tax objects with tax rates in accordance with tax regulations